2020
DOI: 10.35118/apjmbb.2020.028.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Trihoney ameliorates hypercholesterolemia-induced epididymal histopathological changes in male rabbits

Abstract: Hypercholesterolemia has been linked to weight change and histopathological alteration of male reproductive organs. The epididymis was suggested to be an early target of lipid-related infertility and can be dramatically affected by excess intake of a high cholesterol diet. On the other hand, the interest has been increased towards the use of honey as a prophylactic and therapeutic agent for various diseases. Therefore, the purpose of this study is to investigate the effects of Trihoney (a mixture of Trigona, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…These mechanisms are the most likely underlying mechanisms through which Trihoney with its high total phenolic content (TPC) and antioxidant activity improved the testicular histopathological changes and spermatogenesis with a subsequent improvement of testicular weight in this study. The improvements of testicular histopathology and spermatogenesis are the main mechanisms that drive the improvements in the epididymal weight and histopathology in our previously published study (Mohamed et al, 2020).…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…These mechanisms are the most likely underlying mechanisms through which Trihoney with its high total phenolic content (TPC) and antioxidant activity improved the testicular histopathological changes and spermatogenesis with a subsequent improvement of testicular weight in this study. The improvements of testicular histopathology and spermatogenesis are the main mechanisms that drive the improvements in the epididymal weight and histopathology in our previously published study (Mohamed et al, 2020).…”
Section: Discussionsupporting
confidence: 49%
“…Disruption of spermatogenesis with reduction of sperm production that cause testicular weight reduction is one of the main causes of epididymal weight reduction (Creasy & Chapin, 2013). Our previously published study demonstrated that atorvastatin showed no improvement in the relative epididymal weight of hypercholesterolemic rabbits; meanwhile, it caused a worse reduction in the absolute epididymal weight than the administration of high cholesterol diet alone (Mohamed et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One percent cholesterol diet was prepared according to the method of Mohamed et al, (2020). 10 Ten grams of cholesterol powder (Nacalai-Tesque, Japan) were emulsified in 20mL (2%) of coconut oil (Certified Organic, Philippines). The emulsion was then poured onto 970 grams of rabbit pellet and mixed thoroughly.…”
Section: Preparation Of 1% Cholesterol Dietmentioning
confidence: 99%